Effect of pedogenesis on the stable isotopic composition of calcretes and n‐alkanes: Implications for palaeoenvironmental reconstruction. Issue 5 (16th December 2018) - Sarangi, Vijayananda; Kumar, Anurag; Sanyal, Prasanta
Abstract: In a fluvial system, depending on sub‐aerial exposure, non‐pedogenic pond calcretes can be modified into pedogenic calcretes. The present study attempts to understand the effect of sub‐aerial exposure and pedogenesis on calcretes using carbon and oxygen isotopic composition. For this purpose, two profiles (profile‐A and profile‐B) from the same stratigraphic level in Rayka from the western part of India were selected. The profiles are separated by a distance of 500 m and showed differences in calcrete characteristics. In profile‐A, the calcretes showed pedogenic features (root traces and void filling spar) whereas calcretes in profile‐B showed non‐pedogenic characteristics (fine laminations). However, some of the calcretes in profile‐A exhibited remnants of fine laminations suggesting that initially the calcretes had a non‐pedogenic origin but were modified due to pedogenesis. In profile‐A, the carbon and oxygen isotope values of pedogenic calcrete ( δ 13 CPC and δ 18 OPC ) showed more variation compared with non‐pedogenic pond calcretes ( δ 13 CSPC and δ 18 OSPC ) in profile‐B. The δ 13 CPC and δ 13 CSPC values exhibited a spread of 3·0‰ and 1·3‰, respectively, and δ 18 OPC and δ 18 OSPC values showed a spread of 2·3‰ and 1·3‰, respectively. The differences in the isotopic composition between the two profiles suggest that pedogenesis controlled the isotopic inheritance in calcretes. In addition, the carbon isotopic composition of organic matter ( δ 13 COM ) and n ‐alkanes ( δ 13 C n ‐alk ) that forms the basis of palaeovegetational reconstruction have also been measured to understand the effect of pedogenesis on organic matter in both of the profiles. The average δ 13 COM values in profile‐A and profile‐B are −23·4‰ and −21·1‰, respectively. The disparity in δ 13 COM values is a result of the difference in the sources and preservation of organic matter. However, the δ 13 C n ‐alk values show a similar trend in profile‐A and profile‐B, indicating that sources of n ‐alkanes are the same in both of the profiles and δ 13 C n ‐alk values are unaffected by the pedogenic modifications.